PERCEPTION OF MEMBERS OF GAPOKTANHUT WONO LESTARI TOWARDS COMMUNITY FOREST MANAGEMENT IN JATI MULYO VILLAGE, TANJUNG JABUNG TIMUR REGENCY - Ulfa, S. Hut, M. Si, Maria; Muryunika, Rince; Manullang, Agnes Stefany (Sylva Jurnal Ilmu-ilmu Kehutanan, 2024)
One of the HKm management permit holders is Gapoktanhut Wono Lestari based on the Decree of the Minister of Environment and Forestry with Number:SK.5787/MENLH PSKL /PKPS /PSL.0/9/ 2018, ratified on September 2018 concerning IUPHKm in production forest areas still covering an area of ± 93 Ha in Jati Mulyo Village, East Tanjung Jabung Regency, Jambi Province. The community forest program (HKm) can increase community income and also create jobs through every aspect of forest management functions such as planning, organizing, actuating and controlling (POAC). The research was carried out in Jati Mulyo Village, Dendang District, East Tanjung Jabung Regency from July to August 2023. Data was collected by interviews using questionnaires and sampling using the census method with a total number of respondents of 50 (fifty) people. The data analysis method used in this research is using the Likert scale analysis method, then the results of data management in the form of presentations will be converted into qualitative data using descriptive statistical analysis methods. Based on the research conducted, the results showed that respondents had a good view/perception with a percentage of 79.00% regarding the management of Community Forests in Jati Mulyo Village, East Tanjung Jabung Regency. Respondents have a good perception of management based on the planning function with a percentage of 82.36%, based on the organizational function (organizing) of 80.97%, based on the implementation function (actuating) of 76.81% and based on the monitoring (controlling) function of 74.75%. Jati Mulyo Village Community Forest Management by Gapoktanhut Wono Lestari Members based on POAC analysis has been carried out based on the management plan (RKT/RKU) that has been prepared, however it needs to be maximized so that all components of the POAC management function in HKm management can be implemented